S SOSIALISASI PENCEGAHAN DAN PERAWATAN JERAWAT BAGI SISWA SMA NEGERI 1 NAMORAMBE - Rahmi, Sofia - (INSTITUT KESEHATAN DELI HUSADA, 2023)
SMA Negeri I Namorambe is a high school located in Deli Serdang district, North Sumatra province. Most students often sweat and rarely clean their bodies, especially their faces. These students also often eat unhealthy snacks, so their hormonal conditions, especially growth-related problems, become unstable. As a result, health problems often arise, including acne. Delegates of the Faculty of Pharmacy, Deli Husada Deli Tua Institute of Medicine and Medistra Lubuk Pakam Institute of Medicine organized socialization of acne prevention and treatment for high school students. Through socialization, it is hoped that students can further improve personal hygiene, especially facial hygiene, and maintain a healthy lifestyle in the environment.